PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Lina Marlina; Ade Millatus Sa’diyah; Fajar Mauludin (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
This research is motivated by the reality of the field when making initial observations that menunyarat that students are considered less active, less attention to the lessons described by teachers. One of the goals of this research is to improve the learning process by using Think Talk Write learning model which aims to improve student learning outcomes. The research design is done through two cycles, starting from planning, execution, observation, reflection, and continuing with next cycle planning. Classroom Action Research took place from January 12, 2017 to March 42017 by using data collection tools from test results and learning outcomes learning instruments. Students' learning outcomes in each cycle experienced an increase evidenced from the results of the cycle I 73% and 86% cycle II. Reinforced by the average of pretest result in cycle 1 is 54,16 while for result of postest for cycle I is 71,25, mean that in cycle I mean result of student learning up 17,09%, while for postest cycle II average 80.4 means that in cycle II the average of student learning outcomes up 9.15%. Based on the data, if the average pretest of cycle I is 54,16 and posttest result of cycle II 80,4 then the average increase of student learning result from pretest cycle I until post cycle II is 26,24%. Thus it can be concluded that using the Think Talk Write (TTW) model can improve student learning outcomes. So it is recommended for teachers related to education to apply and develop the Think Talk Write (TTW) learning model as an alternative in improving student learning outcomes.